تأثير الذكاء الشعوري في الذكاء المنظمي دراسة تطبيقيه في الشركة العامة للصناعات الكهربائية - الطائي, علي حسون; دهام, علاء (Journal of Economics and Administrative Sciences, 2008)
The two terms"of fective intelligece and organizational intelligence" is it is the emotional intelligency and organizational intelligency"are considered as one of the contemporany terms which the various organizations started to function them in their activities to in crease their efficiency.This study aims at examining those two terms and the possibility of their functioning them in one of the general organizations and the questionnaire is used as atool to gather information that are distributed on asample consists of (50)employees and selected randomly from various organizationl levels.The most important conclusions:1-Theneis aweakness in some of affective intelligence dimensions especially in managing tradition.2- The lack of its sufficiency in the firm understdy,as well as, thereis similar weakness in other dimensions of organizational intelligence like the societies of common in terest with the lack of affective intelligence effectin in the organizational intelligence.